Diagnóstico situacional para identificar los posibles problemas turísticos del cantón Pangua. - Rivas Bonilla, Kimberley Dayanna (2020)
The present investigation exposes the identification of possible tourist problems that Pangua canton possesses, the same ones that are related to the tourist development for which a diagnosis of the sector was made through field visits, application of the PEST-LA matrix, where the main environmental problems were determined, the presence of the garbage dump located a few kilometers from the populated area, deficiency and dissemination tourism promotion, together with the access and the state of internal communication roads of the canton other factor is inhabitants migration as sociocultural problems, regarding to legal component it was determined no control by competent authorities for regularization of establishments that do tourist activities. Finally, SWOT matrix was applied, which proposed a combination of strategies, including road improvement to facilitate products exchange with main cities and facilitate national visitors access; Additionally, to promote tourism as an economic alternative and generating interest in tourism actors to maintain natural resources, which will contribute to the execution of recreational activities. as conclusion it can be noted tourism promotion and dissemination as the main problems that limit the creation of tourism products as an economic alternative, the authorities have neglected the attention to the development of tourism derived from budget prioritization , where tourism has not been exposed as an important source for canton development it is recommended that authorities could carry out projects or generate activities to help the promotion of the sector through an economic model with a tourist focus; In this way the economy subsequently improves life quality for population as a complementary way. By socialization of the present investigation to the authorities and interested people could develop tourism projects and plans can be constructed based on the reality of the canton and its benefit.